Immunoglobulin A in the skin of patients with ankylosing spondylitis. Issue 12 (December 1988) - Collado, A; Sanmarti, R; Bielsa, I; Castel, T; Kanterewicz, E; Cañete, J D; Brancós, M A; Rotes-Querol, J
Abstract : Cutaneous immunofluorescence studies were carried out in 21 patients with ankylosing spondylitis (AS) and the results compared with those for 18 healthy subjects. The most prominent finding was the presence of IgA in dermal vessels of patients with AS (71% compared with 17% of the control group). IgG and IgM cutaneous deposits were also observed in patients with AS, but these results did not differ from those of the control group. A renal biopsy was performed in three of the patients presenting with unexplained microscopic haematuria. One of them had an IgA nephropathy, but no correlation was found between kidney and skin deposits of IgA. These findings suggest that IgA cutaneous deposits in AS are not a marker of IgA nephropathy but stress the role of immunoglobulin A in the pathogenesis of this disease.